Решите уравнение ( 10x – 3 ) + ( 12x – 4 ) = 7 – ( 15 – 22x ).

Решите уравнение ( 10x – 3 ) + ( 12x – 4 ) = 7 – ( 15 – 22x ).
Гость
Ответ(ы) на вопрос:
Гость
( 10x - 3) + ( 12x - 4) = 7 - ( 15 - 22x) 10x - 3 + 12x - 4 = 7 - 15 + 22x 22x - 22x = 7 - 8 0x = - 1 - не имеет смысла,так как на 0делить нельзя. Ответ: корней нет.
Гость
 10x - 3) + ( 12x - 4) = 7 - ( 15 - 22x) 10x - 3 + 12x - 4 = 7 - 15 + 22x 22x - 22x = 7 - 8 0x = - 1 - не имеет смысла,так как на 0делить нельзя. Ответ: корней нет.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы